Peran PARMADE Dalam Membina Masyarakat Muslim Minoritas di Desa Rambung Baru - Sari Dewi Surabina (Medan Resource Center, 2021)
In this study, researchers examine the role of Permade in fostering the understanding of minority Muslim communities in Rambung Baru Village, Deliserdang Regency. Rambung Baru Village is a village located in Deliserdang Regency, North Sumatra Province which still has a small Muslim community in every corner of the area. In this case, several elements of society want the progress of Muslims in the area to form a community organization, namely PERMADE. This researcher refers to how the Muslim community understands Islam and how Permade fosters minority Muslims and how the community responds to the existence of Permade. The purpose of this research is to generate the spirit of understanding Islam in the area. Permade became a forum to equalize the perception among da'I in fostering the Muslim community in this area. Since the formation of Permade, a lot of Islamic knowledge has been seen in the community. With the programs carried out by Permade in the form of a friendship agenda, fardu kifayah, and several other programs. It is hoped that the presence of Permade in Rambung Baru Village will solve the problem of the lack of basic Islamic knowledge that has not been obtained so far and Permade must continue to update the strategies used to attract the public